Exploring the mechanical, dynamical, and thermal stability of Cs2AgBiX6 (X = Br, Cl) for optoelectronic and thermoelectric applications - M. A. Ghebouli; K. Bouferrache; Rabah Boudissa; B. Ghebouli; M. Fatmi; Faisal Katib Alanazi (Scientific Reports)
Abstract This study investigates the mechanical, dynamical, and thermodynamic properties of Cs2AgBiX6(X = Br, Cl) using first-principles calculations. Structural analysis confirms the cubic double perovskite arrangement, with Cs2AgBiCl6 exhibiting a more compact lattice due to the smaller ionic radius of Cl⁻ compared to Br⁻. Mechanical stability is assessed through elastic constants and Born criteria, confirming the robustness of both compounds, with Cs2AgBiCl6 demonstrating higher stiffness and resistance to deformation. Phonon dispersion calculations reveal no imaginary frequencies, verifying their dynamical stability. Thermodynamic analysis explores heat capacity, entropy, Debye temperature, and thermal expansion behavior under varying temperatures and pressures. The results indicate that Cs2AgBiCl6 possesses superior mechanical and thermal stability.